Study of anticonvulsant activity of Valeriana officinalis roots and rhizomes hydroalcoholic extract in mice and relation to nitric oxide - GH Karimi; H Hosseinzadeh; H Bakhtiyari (Institue of Medicinal Plants, ACECR, 2003)
The anticonvulsant effect of Valeriana officinalis roots and rhizomes hydroalcoholic extract was studied, utilizing maximal electroshock (MES) and pentylenetetrazole (PTZ) tests. In the PTZ test, the extract (0.3-3 g/kg, ip) increased the onset time of Tonic Hind Limb Extension dose-dependently. In the MES test, neither of doses showed antiseizure activity. L-NAME (1-10 mg/kg ip) reduced the anticonvulsant effect of extract in the PTZ test. The results suggest that Valeriana officinalis extract could be a candidate for treatment of petitmal seizure and nitric oxide may be involved in this effect.